(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
In clinical practice we usually come across cases with severe tooth wear which requires a full mouth rehabilitation. And management of patients with worn-out dentition was always a tough and complex procedure. For a predictable and favourable treatment outcome a systemic multidisciplinary approach was required. This case report describes the interdisciplinary approach in the treatment of a patient with severe attrition and loss of vertical dimension. After performing endodontic treatment for required teeth, a bite raising transitional prosthesis was given for increasing the VD to acquire essential interocclusal space for post and core buildups and full coverage restorations. After that the porcelain fused to metal permanent restoration was fabricated and scrutinized for stable contact in centric and eccentric relation.